(untitled) (Fiep Bulletin - online, 2014)
This assignment intends to demonstrate the motor progression of a child (GV) that owns hydrocephalus after 8 (eight) activities months of Physical Education in The Program of Motor Activities for Disabled Person - PROAMDE, that is a extension program from Federal University of Amazons - UFAM. When entering the Program at the beginning of school year, GV performed a motive evaluation which verified the level of his basic motive abilities of locomotion, manipulation and balance. During the classes were proposed activities in groups, individual, recreative and in circuits, with goals of developing the fundamental motive abilities as well as the cognitive and affective aspects of the student. When concluding every class is written down in records of individual accompaniment student’s behavior in that day, highlighting the activities that he did and as it did, a help was needed, finally, for then have a base of how the student is progressing. Through the done annotations that GV is observed has been progressing not only in the aspect motor as well as in the cognitive and affective. Today he does not cry anymore in activities that provide develop space notion, how to go pass inside of the tunnel, go pass underneath of a rope and to go pass inside of arcs. GV already rolls sidelong, it crawls with little difficulty and walk in six supports without help. Regarding the abilities of manipulation, GV launch balls with both hands for a target or for a colleague, even though are in a short space, not needing anymore help to perform this movement. Thus, how much earlier a child is stimulated through motive activities, have her disabled or not, better will be his development motor. The ideal so that the child obtains success in some activity is that are provided her that that she manages to accomplish, seeking strategies to stimulate his potentialities.